Measurement of CP violation in B0→D+D− decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; et al. (Physical review letters, 2016)
The CP violation observables S and C in the decay channel B0→D+D− are determined from a sample of proton-proton collisions at center-of-mass energies of 7 and 8 TeV, collected by the LHCb experiment and corresponding to an integrated luminosity of 3 fb−1. The observable S describes CP violation in the interference between mixing and the decay amplitude, and C parametrizes direct CP violation in the decay. The following values are obtained from a flavor-tagged, decay-time-dependent analysis: S=−0.54+0.17−0.16(stat)±0.05(syst), C=0.26+0.18−0.17(stat)±0.02(syst). These values provide evidence for CP violation at a significance level of 4.0 standard deviations. The phase shift due to higher-order standard model corrections is constrained to a small value of Δϕ=−0.16+0.19−0.21 rad.
Im Titel sind die Zahl 0 und die Zeichen + und - hochgestellt
*LHCb Collaboration: R. Aaij, P. D'Argent, S. Bachmann, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, S. Esen, D. Gerick, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kecke, M. Kolpin, K. Kreplin, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Stahl, D. Stemmle, U. Uwer, M. Vesterinen, A. Zhelezov [und 741 weitere Personen]
Gesehen am 03.07.2020